APE (Alat Permainan Edukatif) â€œKebanaâ€ Pada Pembelajaran IPA/Sains di Pengembangan SD/MI - Saputro, Anip Dwi (Holistik: Journal for Islamic Social Sciences, 2019)
Educational instrument (APE) "kebana" in science learning for elementary / MI level students for low grade is a game made from used baskets for fruit basket which is intentionally designed specifically for educational purposes and is multipurpose so as to give students the opportunity to gain new knowledge and enrich his experience. The implementation of APE "kebana" is students formed by several groups and each group advances in turn. The teacher asks the group representative to install batteries on the watch. Each group was asked to observe clockwork and say what time it is now? Students are asked to move artificial needles according to the assignment of the teacher and connect with the correct characteristics. Students are told to arrange puzzles into whole shapes. This can be done by individual, classical and group according to the innovations of the teacher. Students are asked to roll a marble in a marble cave. Students are asked to arrange bowling from used drink bottles that have been filled with lottery-shaped picture cards and then throw plastic balls until it hits one of them or all of the bowling. If bowling falls 1 then thechild is told to pick up a lottery in a dropped used drink bottle and if he drops more than one then the child must choose one to take the lottery. The lottery contains pictures and questions from the teacher about learning science. Children who can answer from lottery tumbar questions then have the right to blow kinang.